2022
DOI: 10.1111/1744-9987.13790
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of acute kidney injury and its association with mortality in patients diagnosed withCOVID‐19 followed up in intensive care unit

Abstract: Introduction:The kidneys are some of the most frequently affected organs during coronavirus disease 2019 . This multicenter study evaluated the incidence of and risk factors for acute kidney injury (AKI) in COVID-19 patients followed up in intensive care unit (ICU) and its association with mortality.Methods: Three hundred twenty-eight patients diagnosed with COVID-19 and hospitalized in ICU were included. Risk factors associated with AKI and mortality were evaluated. Results: Eighty-eight patients (27.9%) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 38 publications
1
6
1
Order By: Relevance
“…The use of CRRT in our critical patients with COVID-19 was consistent with previous epidemiological studies in which the use of CRRT was required in approximately 44% of patients [16]. Many studies reported that AKI is a common complication in critical COVID-19 cases and occurred in 25-76% of cases, with 5-44% of them requiring CRRT [32,33]. About 35-50.9% of patients with AKI in the ICU associated with COVID-19 pneumonia required CRRT in some studies from the United States [9,15].…”
Section: Discussionsupporting
confidence: 88%
“…The use of CRRT in our critical patients with COVID-19 was consistent with previous epidemiological studies in which the use of CRRT was required in approximately 44% of patients [16]. Many studies reported that AKI is a common complication in critical COVID-19 cases and occurred in 25-76% of cases, with 5-44% of them requiring CRRT [32,33]. About 35-50.9% of patients with AKI in the ICU associated with COVID-19 pneumonia required CRRT in some studies from the United States [9,15].…”
Section: Discussionsupporting
confidence: 88%
“…Male gender and hypertension were independently associated with AKI development. These results were expected as these variables were well-known risk factors for AKI in COVID-19 population [3, 25, 26].…”
Section: Discussionmentioning
confidence: 71%
“…Acute kidney injury (AKI) is a common complication of COVID-19, affecting 25-77% of patients admitted to an intensive care unit (ICU) and associated with major challenges for the healthcare team [4,[6][7][8][9][10]. Between 5 and 44% of patients receive kidney replacement therapy (KRT) [11][12][13][14][15][16]. We hypothesised that the incidence of COVID-19 associated AKI and KRT rates had declined since the beginning of the pandemic [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%